In vitro and in vivo antibacterial activity assays of carvacrol: A candidate for development of innovative treatments against KPC-producing Klebsiella pneumoniae. - Gleyce Hellen de Almeida de Souza; Joyce Alencar Dos Santos Radai; Marcia Soares Mattos Vaz; Kesia Esther da Silva; Thiago Leite Fraga; Leticia Spanivello Barbosa; Simone Simionatto (PLoS ONE, 2021)
Dissemination of carbapenem-resistant Klebsiella pneumoniae poses a threat to the successful treatment of bacterial diseases and increases the need for new antibacterial agents development. The objective of this study was to determine the antimicrobial activity of carvacrol against multidrug-resistant K. pneumoniae. Carbapenemase production was detected by MALDI-TOF. The PCR and sequencing showed that the blaKPC-2, blaOXA-48, blaNDM-1, blaCTX-M-8 genes were present in carbapenem-resistant K. pneumoniae strains. The polymyxin-resistant K. pneumoniae strain exhibited alterations in mgrB gene. The antimicrobial activity of carvacrol was evaluated in vitro using broth microdilution and time-kill methods. For this, carbapenem-resistant K. pneumoniae and polymyxin-resistant strains, were evaluated. The in vitro results showed that carvacrol had antimicrobial activity against all isolates evaluated. The survival curves showed that carvacrol eradicated all of the bacterial cells within 4 h. The antimicrobial effect of carvacrol in vivo was determined using a mouse model of infection with Klebsiella pneumoniae carbapenemase (KPC). The treatment with carvacrol was associated with increased survival, and significantly reduced bacterial load in peritoneal lavage. In addition, groups treated with carvacrol, had a significant reduction in the total numbers of white cell and significantly increased of platelets when compared to the untreated group. In vivo and in vitro studies showed that carvacrol regimens exhibited significant antimicrobial activity against KPC-producing K. pneumoniae, making it an interesting candidate for development of alternative treatments.